PROGRAM ACARA ANAK LAPTOP SI UNYIL DI TRANS7 - -, Mahardini (Seni Media Rekam ISI Surakarta, 2010)
This study is to explore the strategy of awakening of The Unyil â€˜Indonesian puppet film at televisionâ€™. â€œThe Unyilâ€ is one of the popular childrenâ€™s show on 1980's era until the early 1990's. Meanwhile â€œLaptop Si Unyilâ€ premiered in Trans7 broadcast on March 19, 2007. The main characters used in this program is a puppet show â€œThe Unyilâ€. This study focuses on the finding of new concept of â€˜The Unyilâ€™ in order to be able to re-life. Some perspectives would be analyzed such as program theme, style of storytelling, the use of narrator, and narrative structure.Keywords: program theme, narrative structure, style of storytelling, the use of anarrator.